Can Minimum Wages Close the Gender Wage Gap? : Evidence from Indonesia - Hallward-Driemeier, Mary; Rijkers, Bob; Waxman, Andrew (World Bank, Washington, DC, 2015)
Using manufacturing plant-level census data, this paper demonstrates that minimum wage increases in Indonesia reduced gender wage gaps among production workers, with heterogeneous impacts by level of education and position of the firm in the wage distribution. Paradoxically, educated women appear to have benefitted the most, particularly in the lower half of the firm average earnings distribution. By contrast, women who did not complete primary education did not benefit on average, and even lost ground in the upper end of the earnings distribution. Minimum wage increases were thus associated with exacerbated gender pay gaps among the least educated, and reduced gender gaps among the best educated production workers. Unconditional quantile regression analysis attests to wage compression and lighthouse effects. Changes in relative employment prospects were limited.